La Frichelette of Thônes. War, Memory and Territorial Identity in Aravis from 1793 to the Age of Internet - Franck Roubeau (Revue de Géographie Alpine)
From the early-19th century to the 1960s Thônes, in the Aravis massif, was known as a strongly Conservative, Roman Catholic area, following tragic events during the French Revolution. In May 1793 local people revolted against the recently instated Republican authorities. It soon became the ‘Savoy Vendée’, staying that way for many years, its memory perpetuated alongside that of its heroine, La Frichelette, executed by firing squad. Her fate, since her death, reveals a commemorative dynamic, with popular and scholarly roots, which has sustained deep-rooted mistrust of novelty and outside changes.